Specific physiological features of inorganic selenium compounds regarding metabolism : in vivo and in vitro investigations with type II diabetic dbdb mice and healthy rats - Müller, Andreas; Justus Liebig University Giessen (My University, 2007)
At present a controversial discussion regarding benefits and risks of selenium (Se) supplements on insulin resistant diabetes and obesity is in progress.The aim of the present studies consequently was to examine molecular coherences and mechanisms behind both aspects of the effects of Se on metabolic processes in different rodent species. Two animal trials of the present studies focussed on the examination of antidiabetic effects of high supranutritional selenate doses in dbdb mice. Two further animal trials of the present studies with healthy growing rats investigated undesirable effects of Se on the development of insulin resistant diabetes and obesity. The main results of the studies were: The oral application of high supranutritional selenate doses also clearly produced antidiabetic effects in type II diabetic dbdb mice with insulin resistance. In contrast selenite application was inefficient for diabetes therapy in dbdb mice. In the present work novel findings on the particular molecular mechanism behind the antidiabetic effects of selenate could be pointed out from the fact that selenate treatment effected a distinct amelioration of insulin resistance, followed by changes in the expression and activity of glycolytic and gluconeogenic key enzymes. Prior studies with type I diabetic animals have linked an increased phosphorylation of downstream proteins in the insulin signalling pathway (beta subunit of the insulin receptor, MAPK, ribosomal S6 kinase) to the antidiabetic virtues of selenate. In the present work it could demonstrated that an increased phosphorylation of insulin signalling proteins and therefore antidiabetic virtues of selenate are based on the inhibition of protein tyrosine phosphatases (PTPs) rather than representing a direct influence of selenate on protein phosphorylation. In this context another original finding of the present work was that selenate s antidiabetic properties are keenly linked to mammalian Se metabolism. The results of an in vitro inhibition test for PTPs showed that PTP inhibition of orally applied selenate (Se +VI) derives from its intermediary reduction to the thiol-reactive selenite oxidation state +IV, acting as the actual PTP inhibitor. On this account it could be concluded that selenate feeding can be matched by the in vitro use of selenite. In the rat trials a number of candidate genes, which may mediate undesirable effects of Se on insulin resistant diabetes and obesity, could be evaluated by means of a microarray screening. In this screening the insulin antagonistic protein tyrosine phosphatase 1B (PTP1B) thereby represented one of the promising genes. The detailed study of PTP1B regulation revealed that the enzyme was up-regulated by both an optimization of GPx1 activity and by dietary Se supply. Thus dispensable Se supplementation led to a dose-dependent increase in PTP1B activity. The results of the present rat studies therefore could point out for the first time a plausible physiological mechanism by which a permanent surplus of Se can promote the development of insulin resistant diabetes and obesity. In conclusion the present studies could contribute to a considerably better understanding of the molecular mechanisms by which high supranutritional selenate doses attain antidiabetic effects concerning insulin resistant type II diabetes. The safety of high supranutritional selenate doses, as required for antidiabetic effects, however has so far only been tested in tissue cultures and in animal models, and it is still questionable if selenate application in therapeutical and thus non-physiological doses can be relevant for diabetes treatment in humans. Secondly the present studies with growing rats could find new aspects how the permanent use of Se supplements, moderately beyond the recommended amounts, may promote the development of insulin resistant diabetes and obesity. In conclusion these results demonstrate the need for future investigations focussing on the influence of Se in metabolic processes. Those investigations should also consider interactions of Se with other antioxidants, with secondary plant substances, as well as the particular nutrition (carbohydrates, sugars, fat, fiber) in order to obtain a better risk assessment. Since the permanent uptake of Se supplements seems to involve risks strict compliance with the current recommendations in human and animal nutrition should be ensured.

Derzeit wird eine kontroverse wissenschaftliche Diskussion über Nutzen und Risiken einer zusätzlichen Supplementierung mit Selen (Se) bezüglich ihres Einflusses auf Typ II-Diabetes und Fettleibigkeit geführt. Die Ziele der vorliegenden Arbeit bestanden somit einerseits darin molekulare Wirkungsmechanismen hinter antidiabetischen Effekten hoher Selenatdosierungen in Bezug auf Typ II-Diabetes zu untersuchen und andererseits mögliche physiologische Erklärungsansätze für eine beschleunigte Entwicklung von Typ II-Diabetes und Fettleibigkeit durch eine permanente Einnahme von Selensupplementen zu finden. Zwei Tierversuche der vorliegenden Arbeit dienten der Untersuchung der antidiabetischen Wirkung hoher Selenatdosierungen auf Typ II-Diabetes. Diese Versuche wurden mit dbdb Mäusen durchgeführt. Zwei weitere Tierexperimente der vorliegenden Arbeit waren der Untersuchung unerwünschter Eigenschaften von Selen in Bezug auf die Entwicklung von Typ II-Diabetes und Fettleibigkeit gewidmet. Diese Versuche wurden mit gesunden heranwachsenden Albinoratten durchgeführt. Folgende Ergebnisse wurden erzielt: Die orale Applikation hoch-supranutritiver Selenatdosierungen hatte auch bei typ II-diabetischen dbdb Mäusen eine deutliches antidiabetisches Potenzial. Die Verabreichung von Selenit hingegen zeigte keinen therapeutischen Effekt. Die vorliegende Arbeit konnte neue Erkenntnisse bezüglich des antidiabetischen Wirkungsmechanismus von Selenat aufzeigen. In früheren Studien an typ I-diabetischen Tiermodellen wurde postuliert, dass die insulinomimetische Wirkung des Selenats auf einer Erhöhung der Phosphorylierung bestimmter Proteine in der Insulinsignalkaskade (beta Untereinheit des Insulinrezeptors, MAPK, ribosomale S6 Kinase) basiert. Im Gegensatz zu diesen Erkenntnissen konnte in der vorliegenden Arbeit aufgezeigt werden, dass die erhöhte Phosphorylierung von Insulinsignalproteinen die Folge einer Inhibierung insulin-antagonistischer Protein Tyrosin Phosphatasen (PTPs) darstellt und nicht auf einem direkten Einfluss des Selenats auf die Proteinphosphorylierung beruht. Darüber hinaus konnte in der vorliegenden Arbeit zum ersten Mal dargestellt werden, dass die antidiabetische Wirkung des Selenats eng mit dem Se Metabolismus von Säugetieren verknüpft ist. Durch einen in vitro Inhibierungstest für PTPs konnte gezeigt werden, dass die inhibierende Wirkung von oral verabreichtem Selenat auf der intermediären Bildung der thiol-reaktiven Selenitoxidationsstufe +IV beruht, welche eine stark inhibierende Wirkung gegenüber PTPs zeigt. Daraus konnte geschlossen werden, dass die orale Selenatverabreichung mit der in vitro Wirkung von Selenit vergleichbar ist. In den Rattenversuchen konnte eine große Anzahl von Kandidatengenen, welche für unerwünschte Wirkungen des Selens bezogen auf die Entwicklung von Typ II-Diabetes und Fettleibigkeit verantwortlich sein könnten, mittels eines Microarray Screenings ermittelt werden. Die insulin-antagonistische Protein Tyrosin Phosphatase 1B (PTP1B), die in der Literatur als ein herausragendes Zielgen im Zusammenhang mit der Entwicklung von Insulinresistenz und Fettleibigkeit beschrieben wird, stellte ein Gen dar, welches durch Se deutlich heraufreguliert wurde. Die detaillierte Untersuchung der PTP1B Regulation zeigte, dass die Enzymaktivität der PTP1B sowohl durch eine Optimierung der GPx1 Aktivität als auch durch die diätetische Selenzufuhr heraufreguliert wird. Eine über den Bedarf hinausgehende Selenversorgung zog eine dosisabhängige Zunahme der PTP1B Aktivität nach sich. Die Ergebnisse der vorliegenden Arbeit konnten somit über die Regulation der PTP1B zum ersten Mal eine plausible physiologische Erklärung für eine begünstigte Entwicklung von Typ II-Diabetes und Fettleibigkeit durch eine permanente bedarfsübersteigende Se-Supplementierung aufzeigen. Zusammenfassend konnte die vorliegende Arbeit neue Beiträge zum besseren Verständnis der molekularen Mechanismen hinter der antidiabetischen Wirkung hoch-supranutritiver Selenatdosierungen leisten. Bezüglich der permanenten Einnahme von bedarfsübersteigenden Se Mengen, konnte die vorliegende Arbeit eine plausible Erklärung für eine fördernde Wirkung von Se auf die Genese von Typ II-Diabetes und Fettsucht geben.
Spezielle physiologische Wirkungen anorganischer Selenverbindungen auf Stoffwechselvorgänge : in vivo- und in vitro-Untersuchungen an typ II-diabetischen dbdb-Mäusen und stoffwechselgesunden Ratten
Keywords: selenium; selenate; diabetes; ddc:630